VOLUNTARY COMPLIANCE: KESELARASAN ANTARA KEPERCAYAAN DAN KEKUASAAN OTORITAS - PRASETYA S, GILANG (Jurnal Akuntansi AKUNESA, 2018)
This study aims to determine the effect of trust in authorities on voluntary tax compliance with the power of authorities as a moderator of trust in authorities. The type of this research is quantitative using primary data obtained from questionnaire. This research uses path analysis test with Partial Least Square program (PLS). The results of this study suggest that trust has a significant effect on voluntary compliance, the higher level of taxpayer trust to the government then the voluntary compliance will increase and power of authorities can weaken the influence of trust on voluntary compliance, the more power taxpayer provide and the more often they exercise their power the more voluntary compliance the trust will effect.Keyword:TrustinAuthorities,PowerofAuthorities, VoluntaryTaxCompliance